The role of professional artistic practice in the pedagogy of artist-teachers in Cape Town - Langeveldt, Bernadette Ann (Centre for Film and Media Studies, 2026)
This qualitative study examined the artist-teacher identity experiences of six artist-teachers (specialist arts teachers) teaching music (n=1), dance (n=2), drama (n=2) and visual art and design (n=1) to primary and secondary learners in schools in Cape Town. The study explored two closely related questions: (a) What roles do the professional artistic practices and experiences of artist-teachers in public schools play in their arts teaching? and (b) How do artist-teachers in schools remain professionally connected to their craft outside the classroom? Data was generated via six individual interviews and a focus group discussion and was later transcribed verbatim. The transcribed data was then inductively analysed by creating codes and categories based on recurring ideas and patterns in the data using a thematic analysis approach. Data analysis yielded the following themes: 1) Artistic practice as a stimulant for arts teaching and learning; 2) Artistic practice as a source of cultural and local industry knowledge; 3) Challenges and constraints to teachers' hybrid identity; 4) Strategies for maintaining teachers' artistic identity; and 5) Recommendations emerging from participants. The findings revealed that the participant artist-teachers define and experience the dual identities of artistteacher as intertwined and symbiotic rather than distanced or separated. The findings also revealed that artistteachers' creative practices and professional experiences were critical and central to their classroom arts pedagogy. They were sources of motivation, inspiration, local cultural knowledge and pedagogical skills development. Their artistic practices were also critical to their holistic sense of self and well-being. Personal, school related, arts industry, and curriculum factors, however, created tensions that adversely affected the teachers' abilities to consistently engage in artistic practice, resulting in felt experiences of failure, disappointment and stagnation amidst feelings of teacher satisfaction. Lack of time and energy were the dominant challenges artist-teachers faced in their attempts to balance their artist-teacher selves. Other constraints were family responsibilities, harsh arts industry realities, minimal school administration support and rigid curriculum content and delivery. This thesis asserts that artist-teachers (specialist arts teachers) working with primary and secondary learners in Cape Town schools significantly value their artistic practices and identities. Despite myriad challenges and constraints, they strongly desire to carve out personal art making space and time and employ networking, collaboration, and flexible approaches to their practice as strategies to maintain their artist identity. This study will be of interest to artists, arts educators, specialist arts teachers, school administrators, university lecturers involved in pre-service arts training and other stakeholders in education.